6k+9-4y=-3

Simple and best practice solution for 6k+9-4y=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k+9-4y=-3 equation:


Simplifying
6k + 9 + -4y = -3

Reorder the terms:
9 + 6k + -4y = -3

Solving
9 + 6k + -4y = -3

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + 6k + -9 + -4y = -3 + -9

Reorder the terms:
9 + -9 + 6k + -4y = -3 + -9

Combine like terms: 9 + -9 = 0
0 + 6k + -4y = -3 + -9
6k + -4y = -3 + -9

Combine like terms: -3 + -9 = -12
6k + -4y = -12

Add '4y' to each side of the equation.
6k + -4y + 4y = -12 + 4y

Combine like terms: -4y + 4y = 0
6k + 0 = -12 + 4y
6k = -12 + 4y

Divide each side by '6'.
k = -2 + 0.6666666667y

Simplifying
k = -2 + 0.6666666667y

See similar equations:

| 13x-16x+19=100 | | -2y+6=x | | y=4x^2+6x-9 | | x+10+x+50= | | 7y+92=-y-12 | | 6(k-1)-(5x-9)=-6 | | 2=3t+-13 | | y=115+10 | | 4x^2-48+k= | | 6x^2-12x-21=0 | | 9x+51=12x | | x+3+x-8+x=5 | | 3x^3+3=0 | | X-3(X-4)=4 | | x+(x-2)+(3+x)=20 | | -7-28m=26m-39m | | 6a+8=36 | | -35-7x=-2x | | C=37.85+.25x | | 8-2b=11 | | -4k-2+6k=-10+3k+6 | | x+(x-2)+(3+2x)=20 | | 18x^2+10a=-11x+4 | | 11+5r=3(r+1) | | k^2+7=-8k | | 2z^2-21z-36= | | -9z+5+7z=-3z+10 | | x+(x-2)+(3+x+2)=20 | | (2/5)m=(15/4) | | 90x^2-180x+360=0 | | s^2-14s+45= | | 6+57x=7 |

Equations solver categories